(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2024)
In an era where the concept of peace is often relegated to the cessation of hostilities, Teaching peace as a matter of justice redefines the field of peace studies. Snauwaert presents a compelling argument for understanding peace not merely as the absence of violence but as a state defined by the ‘presence of justice’ and the active participation of citizens in its maintenance, the ‘political efficacy of citizens’ (2). This book is a profound contribution to the discourse on peace education, asserting that the foundation of a peaceful society is predicated on the development of moral reasoning and justice-oriented citizenship.